New data on the use of grey white-spotted (Świeciechów) flint in south-west Poland - Płonka, Tomasz; Wiśniewski, Andrzej; Bronowicki, Jarosław (Uniwersytet Wrocławski Instytut Archeologii, 2020)
The purpose of this short paper is to characterise the products made of Świeciechów flint which occurred on TRB sites in Lower Silesia. Until now, 31 artefacts made of grey white-spotted flint have been found. They come from 12 sites. The morphology of the artefacts reveals that the manufacture of blanks was based on reduction of blade unidirectional cores. The Świeciechów flint artefacts could have arrived at Lower Silesia in the form of blades or large flakes, finished tools onnot fragmented flakes or blades, as well as tools on heavily fragmented blanks. We may assumethese artefacts were exchanged as gifts. They were highly valued for their rarity, beauty, and utility.